Effects of Spinal Immobilization and Spinal Motion Restriction on Head-Neck Kinematics during Ambulance Transport. (2nd November 2019) - Thézard, Florent; McDonald, Neil; Kriellaars, Dean; Giesbrecht, Gordon; Weldon, Erin; Pryce, Rob T.
Abstract: Objective: To determine the influence of ambulance motion on head-neck (H-N) kinematics and to compare the effectiveness of two spinal precaution (SP) protocols: spinal immobilization (SI) and spinal motion reduction (SMR). Methods: Eighteen healthy volunteers (7 females) underwent a series of standardized ambulance transport tasks, across various speeds, under the two SP protocols in a balanced order ( n = 12 drivers, n = 7 ambulances). Inertial measurement units were placed on participants' heads and sternums, with another affixed to the stretcher mattress frame. Outcome measures included H-N displacement and acceleration. Results: Ambulance accelerations varied across driving tasks (2.5–9.5 m/s 2 ) and speeds (3.0–6.2 m/s 2 ) and resulted in a wide range of H-N displacements (7.2–22.6 deg) and H-N accelerations (1.4–10.9 m/s 2 ). Relative to SMR, SI resulted in reduced H-N motion during turning, accelerating, and speed bumps (1.9–10.7 deg; 0.4–2.6 m/s 2 ), but increased H-N accelerations during abrupt starts/stops and some higher speed tasks (0.4–2.5 m/s 2 ). Ambulance acceleration was moderately correlated to H-N acceleration (r = 0.68) and displacement (r = 0.42). Conclusion: H-N motion was somewhat coupled to ambulance acceleration and varied across a wide range, regardless of SP approach. In general, SI resulted in a modest reduction in H-N displacement and acceleration, with some exceptions. The results inform clinical decisions on SP practice during prehospital transport and demonstrate a novel approach to quantifying H-N motion in prehospital care.